Модель перемагничивания изотропной электротехнической стали в переходном режиме - Зирка, С.Е.; Мороз, Ю.И.; Мороз, Е.Ю. (Технічна електродинаміка, 2012)
A simplified model of conducting ferromagnetic sheet, which describes magnetization of isotropic electrical steels is proposed. The model improvement is achieved by determination of eddy current component of the magnetic field at the sheet surface with the method by Wolman and Kaden, which describes dynamic magnetization of the material with rectangular hysteresis loop. An algorithm of model fitting is proposed, and a comparison of calculated and experimental results has been carried out.